PERANCANGAN BUKU ILUSTRASI DENGAN TEKNIK AQUARELLE SEBAGAI UPAYA MENGENALKAN TOKOH PAHLAWAN 10 NOVEMBER KEPADA SISWA SMP DI SURABAYA - Chandra, Cynthia Joanna; M.A, Karsam; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
Abstract: Surabaya known as City of Heroes since the 10th November incident which known as Heroes Day. The three weeks of war that held on Surabaya many years ago is well known for the biggest war against the foreign nation since the declaration of independent. About 6000-16.000 warriors died, 200 civilians evacuate, and about 2000 peoples from the opponent killed on that incident. It is very equitable if in the future the government established the 10th November incident as the Heroes Day.The fact, not everyone, especially people in Surabaya, knows the people behind the battle. This fact based on the survey that held in 4 junior high schools in Surabaya. The result shows that 63.75% from 80 students can not mention any 10th November heroes beside Bung Tomo. The lack of knowledge about local heroes can cause the lack of appreciatioin amongst the student in Surabaya. According to that problem, then the goal of this research is to design an educational media in the form of illustration book with aquarelle techniques as an attempt to introduce the people behind the 10th November incident towards junior high school students in Surabaya. Keywords: Illustration Book, Heroes